Regulatory Mechanisms of Medium-Term Crop Rotation on Soil Organic Carbon Storage in Red Soils at the Aggregate Level - Xiaomei Gou; Xiangning Wang; Xuemei Wang; Yan Cai; Bing Li; Yi Zhang; Lihong Han (Agriculture, 2025)
Soil organic carbon (OC) storage in crop rotation systems benefits soil productivity and global climate change. However, the regulatory mechanisms and pathways by which soil OC storage is affected under medium-term crop rotation at the aggregate level are not fully understood. Herein, fifteen soil samples from five cropping systems (abandoned farmland, continuous cropping of tobacco, tobacco–pea rotation, continuous cropping of dasheen, and dasheen–ryegrass rotation for over 10 years) were collected from soil at 0 to 20 cm depths in Miyi County, Sichuan Province, China. The soil aggregates and aggregate-associated OC, enzyme activities, and microbial biomass were evaluated. The effects of medium-term crop rotation on soil aggregate-associated OC content and biochemical properties varied between crop types. Specifically, tobacco–pea rotation significantly decreased the proportion of macro-aggregates (0.25–2 mm); the contents of OC, Ca-OC, aliphatic C, alcohols, and phenols; enzyme activities; and fungal biomass in the aggregate fractions, compared with those associated with the continuous cropping of tobacco. In contrast, dasheen–ryegrass rotation significantly increased the recalcitrant OC content, β-glucosidase and polyphenol oxidase activities, microbial biomass in mega-aggregates (>2 mm) and macro-aggregates, and the recalcitrant OC content and enzyme activity in microaggregates (0.053–0.25 mm) and slit clay (<0.053 mm), relative to those in the continuous cropping of dasheen. Moreover, for the continuous-cropping soils, the OC contents were positively correlated with POD activity but negatively correlated with other enzymes. For the rotational soils, the OC content was positively related to the Fe/Al-OC, aromatic-C, aliphatic-C, and microbial biomass contents but negatively related to the carbohydrate content. The increased OC content was driven by the microbial biomass in the aggregate fractions, and medium-term crop rotation changed the negative effect of microorganisms on the OC content into a positive effect at the aggregate level. Overall, medium-term crop rotation enhances OC storage by improving soil structural stability and microbial community dynamics.